alpha-helical peptide containing N,N-dimethyl lysine residues displays low-nanomolar and highly specific binding to RRE RNA - Hyun, Soonsil; Kim, Hyun Jin; Lee, Nam Ju; Lee, Kyung Hyun; Lee, Yeongran; Ahn, Dae Ro; Kim, Keysun; Jeong, Sunjoo; Yu, Jaehoon (AMER CHEMICAL SOC, 2007)
The combinatorial introduction of N,N-dimethyl-Lys groups into Lys-rich alpha-helical peptides and measuring affinities against RRE RNA were carried out. Peptide-g, in which two Lys were replaced by N,N-dimethyl-Lys at 3 and 9 positions, showed low-nanomolar affinity, which is almost the same value as Rev peptide, the natural RRE ligand. Moreover, peptide-g displays a compatible binding specificity as Rev peptide. The effects of the positions of Lys N,N-dimethylation on the specificity of RNA binding could serve as the basis of a new strategy for the design of novel agents against RNAs. The results support that nature may use N-methylation as a post-translational modification to enhance specific peptide-RNA interactions.